What training do teachers need?: Why theory is necessary to good teaching. (November 2015) - Orchard, Janet; Winch, Christopher
Abstract : Recent years have seen a concerted and systematic move towards a school‐led system of initial teacher training in England. The role of universities, and particularly their part in engaging new teachers with educational theory, has been radically challenged. Only around half of new entrants to the profession now follow university‐based training routes. These seismic changes to teacher education have been driven through with a minimum of formal consultation or public debate. In this urgent and compelling pamphlet, Janet Orchard and Christopher Winch argue for a conception of teachers as professionals who require a deep understanding of the conceptual, empirical and normative dimensions of educational practice. They explain why university education departments are better placed than schools to help beginning teachers acquire that understanding. And they propose a significant expansion of initial teacher education, with full licensure contingent on completion of both a preliminary teaching qualification and a higher grade apprenticeship in the first two years of employment. Teachers need educational theory because they must understand what they are doing and why they are doing it, and must be able to think intelligently about how to do it better. At present, universities have the capacity and the expertise to meet this need. But they may not have it for much longer if the shift to school‐based teacher education continues unabated.